1991
DOI: 10.1002/aja.1001900404
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the morphology of the goat epididymis: A light microscopic and ultrastructural study

Abstract: The goat epididymis, based on morphological differences, was divided into five regions; regions I and II, and the proximal part of region III constituted the head; the distal part of region III and region IV, the body; and region V, the tail. The epithelium of all regions contained principal and basal epithelial cells and intraepithelial lymphocytes and macrophages. In addition, regions II to IV also contained a few apical cells. Clear cells were absent. The epithelium varied in height from the tallest in regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 79 publications
5
53
1
5
Order By: Relevance
“…Principal cells possess a well-developed Golgi apparatus and numerous rough endoplasmic reticulum cisternae, suggesting that these cells are able to synthesize and secrete proteins or glycoproteins, similarly to what is observed for other mammalian species (Hamilton;Robaire & Hermo;Goyal & Williams, 1991;Arrighi et al).…”
Section: Discussionmentioning
confidence: 88%
“…Principal cells possess a well-developed Golgi apparatus and numerous rough endoplasmic reticulum cisternae, suggesting that these cells are able to synthesize and secrete proteins or glycoproteins, similarly to what is observed for other mammalian species (Hamilton;Robaire & Hermo;Goyal & Williams, 1991;Arrighi et al).…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, a few apical cells have been reported in the tail region of the cat epididymis (Arrighi et al 1986, Viotto et al 1996. Basal cells lie on the basal lamina and are characterized by scanty organelles as observed in the goat epididymis (Goyal & Williams 1991). Dadoune (1981) reported that the basal cells function is to renew the principal cells in the epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…The fine structure of the epididymis of the mammals has been previously described (Hamilton 1975, Goyal & Williams 1991, Orsi et al 1994, Schimming & Vicentini 2001, Lorenzana et al 2007, Beu et al 2009). The lining epithelium of cauda epididymidis in the mongrel dogs contains four cell types: principal, clear, basal and apical cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations